Optimalisasi Pemanfaatan Marketplace Shopee sebagai Platform dalam Mendukung Strategi Komunikasi Pemasaran pada Toko Tabriizhijab - Muhamad Restu Febfour Herman; Ridma Meltareza (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
In the 4.0 era, technological advances offer significant opportunities, especially for entrepreneurs who develop their businesses through online platforms such as the Shopee e-commerce marketplace. This study examines the use of Shopee as a marketing communication medium by the Tabriizhijab store. Using a qualitative research method with a descriptive approach, this study is able to describe the digital marketing strategy implemented by the Tabriizhijab store owner through the use of various Shopee features such as store vouchers, free shipping, Shopee Live, Shopee Feed, and paid advertising. The findings of this study indicate that Shopee has a significant impact on improving store sales performance. However, it turns out that several challenges still exist, such as a limited understanding of Shopee features that can cause owners to be left behind by Shopee marketing trends, intense price competition between other sellers who offer lower prices for their products, a lack of specialized personnel to handle digital marketing that leads to less than optimal store management, and difficulties in committing to providing responsive service to consumers. Despite facing these challenges, through effective communication strategies, appropriate and optimal use of social media, and improving service quality, Tabriizhijab has been able to build a positive brand image and increase consumer purchasing interest. This study highlights the importance of an appropriate digital marketing communication strategy amidst increasingly fierce market competition. Furthermore, the study emphasizes the importance of managing and utilizing consumer data obtained through platforms like Shopee to formulate more effective and targeted marketing strategies. By utilizing available analytics features, Toko Tabriizhijab can better understand consumer behavior, product preferences, and evolving market trends. This allows the store to adjust its marketing strategy, offer more relevant promotions, and improve the overall customer experience.